User Assessment of Livin by Mandiri - Zoel Hutabarat; Gladys T. Evidente (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
This research was conducted with the aim of finding out customer ratings of the use of a digital banking by the community, especially for digital banking Livin by Mandiri as a case study. The hypothesis in this study has a positive impact, where even with the risk of using digital banking, it can also provide positive results for services. For this study, purposive sampling was carried out from Livin by Mandiri users as respondents. This study has collected 2,023 respondents and used a Likert scale of 1-5. From the results of this study, perceived usefulness is the variable with the highest results, which explains how people's ability to use technology is one of the highest determining factors in using digital banking Livin by Mandiri.